An Intrusion Detection System Based on Hybrid of Artificial Neural Network (ANN) and Magnetic Optimization Algorithm (MOA) - Wahab, Siti Norwahidayah; Sulaiman, Noor Suhana; Abdul Aziz, Noraniah; Zakaria, Nur Liyana; Abd Aziz, Ainal Amirah (International Journal of Integrated Engineering, 2022)
Intrusion Detection System is a type of security application that protects computer and network systems. A variety of techniques have been proposed to increase IDS accuracy. This research study focuses on improving an IDS detection performance by combining an Artificial Neural Network (ANN) with a Magnetic Optimization Algorithm (MOA), with the goal of increasing the classification rate and achieving high detection accuracy in IDS. The suggested ANNMOA result demonstrated that it is possible to improve IDS accuracy by up to 98.5 percent.